Manabu! Hiragana: A Japanese Hiragana Mobile Learning Application - Tan, Qian Ying; Murli, Norhanifah (Applied Information Technology And Computer Science, 2022)
Japanese language is the thirteenth most spoken language in the world, with 126 million people speaking it as their native language. There is no denying that Japanese has getting more popular and familiar with people. Traces of Japan can be seen in most countries, such as Japan town can be found in some countries, followed by Japanese animation which is popular all over the world. However, there are many similar hiragana learning software on the market, but each has its own characteristics and disadvantages. Therefore, this project aims to implement an interactive basic Hiragana mobile learning application for children based on a gamification approach by using Multimedia Mobile Content Development(MMCD) methodology. Satisfactory results with 90% of respondents strongly agreed and agreed with the statement and it can be concluded that Manabu! Hiragana is suitable for learning Hiragana.